The growth potential of the Japanese economy - Kurihara, Kenneth K. (Baltimore : Johns Hopkins Press, 1971)
The book offers an analysis of the fundamental forces governing the speed and pattern of Japanese economic growth not only at present but in the decades ahead.
Includes bibliographical references: p. 141-144.
osa 15/05/2018
Loans
Keywords: Economic history; Economic growth; Economic development; Japan